APPLICATION OF ROLE PLAYING TECHNIQUES IN IMPROVING THE SPEAKING ABILITY OF STUDENTS - Efi Lutfiyah Arifin (Universitas Kuningan, 2021)
In globalization era, the competition in working world is getting tougher which demands that students speak English fluency. But in reality, there are still many students in MAN 2 Kuningan who find it difficult because learning is still teacher-centred so that students are less active in learning. Based on these problems, the researcher formulated the formulation of the problem; How is the role playing techniques in teaching speaking narrative text for XII IPA-2 class pf MAN 2 Kuningan? The purpose is to determine the use of role playing techniques in improving the speaking ability of XII IPA 2 class. This research method uses 3-cycle CAR procedure including planning, action, observation, and reflection. The subjects studied are 29 students of XII IPA 2, the research location is in MAN 2 Kuningan. Data collection techniques are by using observation sheets and questionnaire sheets. Research achievement targets: Research will be declared successful if at least 70% of the number of students obtain a KKM score (75) in learning to speak on Narative text material. While the indicators of student perception and impression are shown when students answer the questionnaire statement with a percentage of at least 70% - 79%. The results can be concluded that role playing method is able to improve speaking skills on narative text.Keywords: speaking; ability; narrative; learning; role playing